2013
DOI: 10.1002/adfm.201302091
|View full text |Cite
|
Sign up to set email alerts
|

Highly Luminescent Covalently Linked Silicon Nanocrystal/Polystyrene Hybrid Functional Materials: Synthesis, Properties, and Processability

Abstract: Silicon nanocrystals (SiNCs) have received much attention because of their exquisitely tunable photoluminescent response, biocompatibility, and the promise that they may supplant their CdSe quantum dot counterparts in many practical applications. One attractive strategy that promises to extend and even enhance the utility of SiNCs is their incorporation into NC/polymer hybrids. Unfortunately, methods employed to prepare hybrid materials of this type from traditional compound semiconductor (e.g., CdSe) quantum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
61
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 70 publications
1
61
0
Order By: Relevance
“…Interestingly, we found that the quenching process is a prerequisite step for inducing the subsequent polymerization reaction; in other words, no polymerization reaction takes place in the absence of resultant chemical species from the reaction between the LiAlH 4 and CuSO 4 under the condition conducted here, i.e., heating at around 120 C for 12 h in Ar. Although the styrene has been well known to undergo polymerization at elevated temperatures due to the formation of thermally self-initiated radicals via a DielseAlder cycloaddition [32,36], the reaction conditions in this study such concentration of styrene to solvent (3e300 mL), temperature (120 C), time (12 h) were not adequate to induce the polymerization. To simply examine the nature of catalysis, three controlled experiments were performed in parallel as summarized in Table S1 in Supplementary Information.…”
Section: Synthesis Of Si Qdepolystyrene (Si Qdeps) Polymersmentioning
confidence: 96%
See 2 more Smart Citations
“…Interestingly, we found that the quenching process is a prerequisite step for inducing the subsequent polymerization reaction; in other words, no polymerization reaction takes place in the absence of resultant chemical species from the reaction between the LiAlH 4 and CuSO 4 under the condition conducted here, i.e., heating at around 120 C for 12 h in Ar. Although the styrene has been well known to undergo polymerization at elevated temperatures due to the formation of thermally self-initiated radicals via a DielseAlder cycloaddition [32,36], the reaction conditions in this study such concentration of styrene to solvent (3e300 mL), temperature (120 C), time (12 h) were not adequate to induce the polymerization. To simply examine the nature of catalysis, three controlled experiments were performed in parallel as summarized in Table S1 in Supplementary Information.…”
Section: Synthesis Of Si Qdepolystyrene (Si Qdeps) Polymersmentioning
confidence: 96%
“…Although this one-pot synthetic approach gave rise to enhanced stability of the Si QDs and new functionality as well, it possessed fundamental limitations in fine control of content and concentration of the Si QDs in the nanocomposite. On the other hand, Yang et al [32] also reported the synthesis of Si QDepolystyrene nanocomposite (or Si NC/polystyrene hybrid, as named in the report) by the similar reaction manner, in which highly luminescent well-defined Si NCs were used. Though the authors demonstrated the variation of Si NC concentration in the nanocomposite (or hybrid) by simply varying the amount of H-Si QD which was reacted with the styrene monomer, the variation of the Si NC concentration was limited in a few weight% (wt%) range such as 0.8, 1.6, and 2.4 wt%, and longer reaction time was required for the higher Si NC-concentrated nanocomposites (e.g., 15 h and 59 h for the 0.8 and 2.4 wt% cases, respectively) [32].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…What is remarkable is the notable intensification of research on bottom-up synthesized forms of nanostructured silicon for everything other than microelectronics. [3][4][5][6] Moreover, the purported nontoxicity 7 and biocompatibility 8,9 of nanometer scale silicon allows it to be marketed as a "Green" material in the emerging field of medical theranostics. One can easily find a long list highlighting prominent reports for nanometer scale silicon in the recent literature.…”
Section: Introductionmentioning
confidence: 99%
“…Other previous, well-established methods for achieving nanoparticle incorporation into a polymer film include supercritical fluid deposition (SFD), in which nanoparticles are synthesised in-situ by a wet chemical reduction of a metal salt within the polymer matrix [7], and the 'casting' method, in which the matrix is polymerised around the nanoparticles [8]. However, both inherently require synthesis of one component within or around the other, which naturally affords limited control over polymer dispersity and morphology, and nanoparticle size and/or crystal phase.…”
Section: Introductionmentioning
confidence: 99%